Stigma toward people with mental disorders - Ihalainen, Ninni (fi=Turun yliopisto|en=University of Turku|, 2023)
The aim of this study was to gain an understanding of the stigma toward people with mental disorders in health care and society. The study was carried out as a mixed methods study that included four phases. First, the perceptions and associated factors of self-stigma among clients (n=898) in outpatient psychiatric services were investigated. Second, the topic of stigma in the curriculums of general nurse education programs at universities of applied sciences (n=11) was investigated. Third, the stigmatizing attitudes and associated factors that primary health care nurses (n=218) had toward people with mental disorders are described. Fourth, a systematic literature review of 55 studies and a meta-analysis of 45 interventions were performed, aiming to describe interventions to reduce stigma and effectiveness of domains of the interventions. Quantitative data were analyzed with statistical methods, and qualitative data also with narrative analysis. According to the results of four phases, first, self-stigma exists among clients with mental disorders. Clients with affective disorders have higher self-stigma than those with psychotic disorders. Long durations of illness and depressive symptoms were also associated with self-stigma. Second, in nursing education at universities of applied sciences, the descriptions of stigma varied in the the different curriculums regarding stigma. Stigma was included only to a limited extent in the content of the courses; only two curriculums out of eleven curriculums included a clear description of stigma. Third, in primary health care, nurses had both positive and stigmatizing attitudes toward people with mental disorders. Positive attitudes were associated with nurses being older and having additional training in the field of mental health. Fourth, descriptions of interventions were at times unstructured and limited. The effectiveness of the interventions to reduce stigma proved to be effective in domains. Stigma toward people with mental disorders is a multifaceted phenomenon that can be viewed from many angles in health care and society. More actions are needed to prevent self-stigma. Therefore, students should be educated about stigma and health care professionals should have access to regular additional mental health training. Effective interventions for stigma reduction decrease stigma among people with mental disorders and increase positive attitudes held by nurses. More research is needed to increase awareness and strengthen understanding about stigma toward people with mental disorders.

Mielenterveyshäiriötä sairastaviin ihmisiin kohdistuva stigma Tutkimuksen tavoitteena oli saada ymmärrystä stigmasta (häpeäleima), joka kohdistuu mielenterveyshäiriötä sairastaviin ihmisiin terveydenhuollossa ja yhteiskunnassa. Tutkimus toteutettiin monimenetelmätutkimuksena neljässä vaiheessa. Ensimmäisessä vaiheessa selvitettiin psykiatrian avohoidossa olevien mielenterveysasiakkaiden (n=898) näkemyksiä itsestigmasta ja yhteydessä olevia tekijöitä. Toisessa vaiheessa selvitettiin sitä, miten stigman opetus kohdistuu sairaanhoitajakoulutuksen opetussuunnitelmiin ammattikorkeakouluissa (n=11). Kolmannessa vaiheessa kuvattiin perusterveydenhuollossa työskentelevien hoitajien (n=218) leimaavia asenteita mielenterveysasiakasta kohtaan ja yhteydessä olevia tekijöitä. Neljännessä vaiheessa toteutettiin systemaattinen kirjallisuuskatsaus (55 tutkimusta) kuvaamaan interventioita ja meta-analyysin avulla tarkasteltiin interventioiden (n=45) osa-alueiden vaikuttavuutta stigman vähentämisessä. Määrälliset aineistot analysoitiin tilastollisilla menetelmillä ja laadulliset aineistot myös narratiivista analyysia käyttäen. Tulosten perusteella ensinnäkin mielenterveysasiakkaalla esiintyi itsestigmaa; mielialahäiriötä sairastavilla asiakkailla itsestigmaa oli enemmän kuin psykoosia sairastavilla asiakkailla. Itsestigmaan oli yhteydessä myös pitkä sairaudenkesto ja masennusoireet. Toiseksi opetussuunnitelmien kuvaukset vaihtelivat stigman osalta. Stigman opetus sisältyi vähäisessä määrin opetussuunnitelmiin; vain kahdessa opetussuunnitelmassa löytyi selvä kuvaus stigmasta. Kolmanneksi perusterveydenhuollossa hoitajilla oli sekä myönteisiä että leimaavia asenteita mielenterveysasiakasta kohtaan. Myönteisempiin asenteisiin olivat yhteydessä hoitajan vanhempi ikä ja mielenterveysalan lisäkoulutus. Neljänneksi stigmaa vähentäviä interventioita oli kuvattu vaihtelevasti. Interventioiden eri osa-alueet osoittautuivat vaikuttaviksi menetelmiksi stigman vähentämisessä. Stigma on monitasoinen ilmiö, jota voi tarkastella useasta eri kulmasta terveydenhuollossa ja yhteiskunnassa. Tarvitaan lisää toimia mielenterveysasiakkaiden itsestigman välttämiseksi. Stigmaan liittyvä koulutus sairaanhoidon opiskelijoille ja säännöllisesti tarjottu mielenterveysalan lisäkoulutus terveydenhuollon ammattilaisille on tärkeää. Vaikuttaviksi osoittautuneet interventiot vähentävät stigmaa ja lisäävät hoitajien myönteisiä asenteita. Tarvitaan lisää tutkimusta stigman tietoisuuden lisäämiseksi ja ymmärtämiseksi.